Investigatio n into short term behaviors of embedded laminated glass connections with various configurations. (23rd August 2021) - Zhao, Chenjun; Yang, Jian; Wang, Xing-er; Ren, Minggen; Azim, Iftikhar
Highlights: The structural behaviors of embedded laminated connections were tested under pull-out load. Key factors such as outmost glass type, thickness of middle glass and dimension of metal insert were examined. Three types of failure modes were classified based on the experimental data and observations. Parametric study using fine numerical models was conducted to analyze the failure mechanism. A simplified analytic approach was proposed to predict the failure mode and ultimate load capacity. Abstract: This study firstly presents an experimental program for investigating the structural behavior of embedded laminated connection (ELC) under pull-out load, including pull-out response as well as the onset and evolution of fracture damage. Several key factors, including the type of outmost glass layer, the thickness of the middle glass layer and the dimension of the metal insert, were examined and their influences were discussed. Three types of distinct failure modes are classified, namely, the brittle failure mode, the progressive failure mode and the delamination failure mode. The experimental results reveal that the use of tempered glass as outmost glass can generate a progressive failure mode, which significantly increase the ultimate capacity (nearly 80%) and exhibit greater ductility when comparing with that of annealed glass having brittle failure mode. The delamination failure mode due to adopting smaller metal insert is found to reduce more than 80% of the ultimate pull-out capacity. A fine numerical model was then used to analyze the failure mechanism in each failure mode. It was followed by a parametric study considering the embedded depth of metal insert and the thickness of outmost and middle glass, which was combined with the experimental data to further support the development of a simplified analytical model for calculating the load capacity and assessing the failure mode of ELC.